2002
DOI: 10.1016/s0014-5793(02)03228-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus anthracis lethal toxin on human peripheral blood mononuclear cells

Abstract: Lethal toxin (LeTx) plays a central role in anthrax pathogenesis, however a cytotoxicity of LeTx has been difficult to demonstrate in vitro. No cytolytic effect has been reported for human cells, in contrast to murine cell lines, indicating that cell lysis can not be considered as a marker of LeTx activity. We have recently shown that murine macrophage‐like RAW 264.7 cells treated with LeTx or infected with anthrax spores underwent changes typical of apoptotic death. Here we demonstrate that cells from human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 39 publications
4
92
1
Order By: Relevance
“…4 C and D). In vitro, lethal toxin induces apoptosis by cleaving mitogenactivated protein kinase kinases (23,24). Our analysis illustrates this specific pathologic damage caused by lethal toxin in vivo.…”
Section: Resultsmentioning
confidence: 66%
“…4 C and D). In vitro, lethal toxin induces apoptosis by cleaving mitogenactivated protein kinase kinases (23,24). Our analysis illustrates this specific pathologic damage caused by lethal toxin in vivo.…”
Section: Resultsmentioning
confidence: 66%
“…Recent studies have shown deleterious effects of the toxin not only on other types of APCs (e.g., dendritic cells) (25), but also on non-leukocytes such as human endothelial cells (26). Pro-apoptotic effects of anthrax LT treatment on unpurified human PBMC have been reported (14), but direct effects on purified T cells have not been previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the effect of anthrax LT on a variety of functions of Jurkat cells in our culture conditions, because anthrax LT has been reported to have a pro-apoptotic effect on PBMC (14). As shown in Fig.…”
Section: Jurkat Cell Proliferation Tcr-dependent Calcium Mobilizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…18,21,41,[55][56][57][58][59][60][61][62][63][64] Viruses exploit apoptotic processes as well, especially reducing the death of virally infected cells to facilitate intracellular viral replication. The viral reprogramming of cell death, in contrast, reflects a distinct approach.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%